Seven Earths in the Qur’anic Worldview: An Epistemological Study of Classical and Modern Tafsir - A. Sholahudin Akhyar; Lusi Ismayenti (Bulletin of Islamic Research, 2026)
Purpose – Cosmological verses of the Qur’an have long been a point of convergence and tension between Qur’anic exegesis and modern scientific thought. Among these, QS. At-Talaq [65]:12 is unique in referring to the “seven earths” (wa mina al-arḍi mithlahunna). This study aims to compare the interpretations of the concept of the seven earths in the exegeses of Ibn Kathīr and Ibn ‘Āshūr and to examine their epistemological implications for contemporary studies of Qur’anic cosmology. Design/methodology/approach – This study employs a qualitative descriptive-comparative approach based on library research. Primary data consist of the exegetical works of Ibn Kathīr and Ibn ‘Āshūr, which are analyzed through comparative textual analysis to identify differences in interpretive methodology, epistemological orientation, and cosmological paradigms. Findings – The study reveals two fundamentally different interpretive paradigms. Ibn Kathīr, employing the tafsīr bi al-ma’thūr approach, interprets the seven earths literally as layered realms supported by prophetic traditions and reports from the Companions, resulting in a vertically structured metaphysical cosmology. In contrast, Ibn ‘Āshūr adopts a rational-philological approach, interpreting the expression as referring to seven regions or continents based on linguistic analysis and openness to empirical knowledge, thereby constructing a horizontal and empirically oriented cosmological model. These contrasting interpretations demonstrate that cosmological exegesis is shaped not only by the Qur’anic text but also by the epistemological frameworks and intellectual horizons of the exegetes. Research implications/limitations – The study is limited to two major exegetical traditions and does not include broader comparative analysis with contemporary scientific or modern exegetical perspectives. Future research may expand the discussion by incorporating interdisciplinary approaches involving cosmology, philosophy of science, and modern Qur’anic interpretation. Originality/value – This study contributes to the field of Qur’anic cosmology by demonstrating that debates over the concept of the seven earths are fundamentally methodological and epistemological rather than questions of scientific correctness. It offers a balanced framework for fostering constructive dialogue between Qur’anic exegesis and modern science while preserving the epistemic integrity of revelation and remaining open to the advancement of human knowledge.